Abses Tiroid pada Pasien dengan Infeksi HIV: Laporan Kasus - Diah Pradnya Paramita; Made Ratna Saraswati (PT Dexa Medica, 2026)
Thyroid abscess is a rare infectious condition as the thyroid gland is completely enclosed by a fibrous capsule, has an iodine-rich environment, an abundant blood supply, and effective lymphatic drainage. Thyroid abscess occurs more frequentlyin patients with pre-existing thyroid anatomical abnormalities or immunocompromised conditions. Underlying thyroid diseases, such as thyroid nodules or thyroid malignancy, represent important predisposing factors. Only approximately 8% of thyroid abscess cases have been reported in the adult population. Case report: A 71-year-old man presented presenting with right-sided neck pain, fever, and odynophagia for seven days prior to admission. Physical examination revealed a 7 × 5 cm mass in the right cervical region with a smooth surface, firm-rubbery consistency, movement with swallowing, and tenderness on palpation. Thyroid ultrasonography demonstrated a cystic lesion with a solid component and internal echoes. Fine-needle aspiration biopsy revealed polymorphonuclear inflammatory cells consisting of neutrophils and lymphocytes. The patient was also newly diagnosed with human immunodeficiency virus (HIV) infection and had subclinical hypothyroidism. A history of thyroid nodules may represent a significant risk factor for the development of thyroid abscess. In this case, the administration of broad-spectrum systemic antibiotics resulted in a favourable clinical response.